Relative anterior spinal overgrowth in mild and moderate adolescent idiopathic scoliosis: a retrospective study - Haoyang Zhang; Xin Ye; Hongjiao Wu; Yi Shen; Yingsen Pan; Xiaoming Ying; Jiaying He (Scientific Reports)
Abstract To determine whether relative anterior spinal overgrowth (RASO) occurs regardless of scoliosis segments and severity, and to explore the pattern of vertebral body height changes in adolescent idiopathic scoliosis (AIS). A total of 125 AIS and 179 non-scoliotic adolescents were enrolled. The anterior vertebral body height (VBHa) and posterior vertebral body height (VBHp) were measured on lateral spine radiographs, and the VBHa/VBHp ratio was calculated. The ratios were compared between the two groups and across scoliosis segments in the AIS group. The correlation between scoliosis severity and vertebral ratios, as well as the relationship between the apex vertebra’s ratio and Cobb angle, was analyzed. Results showed that the VBHa/VBHp ratios were higher in the AIS group than the control group from T6 to L5 (P < 0.001), with increasing ratios from T7 to T10 and L1 to L5. No significant differences were found across scoliosis segments. Pearson analysis showed positive correlations between scoliosis severity and ratios at T7, T8, and T11 (P < 0.05), and a negative correlation at L5 (P < 0.05). No correlation was found between the apex vertebra’s ratio and the Cobb angle. In conclusion, RASO is common in mild to moderate AIS and may help maintain spinal function.